Clinical supervision for the implementation of Math Curriculum: A proposal for Costa Rican education managers - León Fuentes, Hannia (2016)
This article contains a clinical supervision proposal for Costa Rican education managers in the implementation of the Math Curriculum. This document includes relevant aspects of the current curriculum, the role of the education manager in supervision, as well as a guide for clinical supervision which contains four stages: pre-observation, observation, analysis and post-observation. Its contribution lies in the reflection that can be achieved by both, teachers and principals alike, ensuring success in the teaching and learning of Math.